A comparison of Ti-6Al-4V in-situ alloying in Selective Laser Melting using simply-mixed and satellited powder blend feedstocks - Simonelli, Marco; Aboulkhair, Nesma T.; Cohen, Philip; Murray, James W.; Clare, Adam T.; Tuck, Chris; Hague, Richard J.M. (Elsevier, 2018)
In-situ alloying within laser powder-bed fusion, specifically Selective Laser Melting (SLM), has been investigated for the formulation of novel alloys from elemental powders to extend the benefits offered by these technologies. Inadequate preparation of the powder feedstock prior to in-situ alloying can yield inhomogeneous microstructures, often deteriorating the mechanical performance of the deposited parts. The present work was designed to assess the use of the ‘satelliting’ method to create powder feedstocks for in-situ laser powder-bed fusion. The research was carried out on Ti-6Al-4V. Ti-6Al-4V feedstocks obtained by mixing or satelliting elemental powders were investigated and compared to a reference pre-alloyed material. The processability of the different feedstocks was assessed by comparing the microstructure of the deposits originating from the different powder blends. Results show that the powder percolation and particle size distribution of the feedstocks translate in deposited microstructures exhibiting different porosity, elemental segregation, and average grain size, revealing the impact of the powder blend characteristics on the laser energy absorbance and solidification of the alloy. This study provides fundamental insights of how to formulate powder feedstock and aims to support future research activities on the design and development of new alloys for use in powder-based additive manufacturing.